Cooling tower system as teaching aids tools for vocational college and Air Conditioning Technology Program - Zahari, Balqis; Abdul Rahman, Khairul Anuar; Rahim, Mohd Bekri; Yunus, Faizal Amin Nur (Penerbit UTHM, 2021)
The research was conducted to develop a cooling tower system as teaching aids tools for vocational college and Air Conditioning Technology Program. The research was done to enhance student understanding about cooling tower system. In this study, researchers have used the ADDIE model as a guide to develop a cooling tower model. Next, the product was verified by five experts once developed. The result showed the product design is good as a portable cooling tower system, and also suits the usability as teaching aids tools. In conclusion, this cooling tower system can be used during teaching and learning sessions and can facilitate students' understanding of the cooling towers subtopic. Besides, this cooling tower system can be introduced for the purpose of upgrading and can be applied in vocational college, vocational school secondary school, public and private institution of higher learning.